Architecture of a mammalian glomerular domain revealed by novel volume electroporation using nanoengineered microelectrodes - Schwarz, Daniel; Bosch, C.; Feinauer, C.; Whiteley, I.; Margrie, T. W.; Cutforth, T.; Schaefer, Andreas T. (Nature Communications, 2018)
Microcircuit tracing reconstructions often rely on statistical labeling that may not detect all inputs and outputs of a microcircuit. Here the authors employ a novel electroporation approach to densely label neurons and demonstrate its ability to identify sparse anatomical features in the olfactory glomerulus.